Transforming legal education teaching and learning: The Remote Communication Technology - Ali Mohamed, Ashgar Ali; Amirnuddin, Puteri Sofia; Ahmad, Muhamad Hassan; Ramalingam, Chithra Latha (Lexis Nexis Malaysia Sdn Bhd, 2021)
The recent revolutionisation of the courtrooms with digitalization such as live-streaming or broadcasting of the court’s proceedings would undeniably allow the public virtual entry into the courtrooms. Hence, this article highlights the need for the law faculties and law schools to embrace the remote communication technology in the teaching and learning of legal education which undeniably is an important tool for the graduate’s future employability. It would be submitted that the law faculties and law schools in Malaysia must continue the e-learning beyond the COVID-19 period. The 'old-fashioned' face-to-face interactions between students and lecturers must be adjusted to imbue the remote communication technology. Further, the regulatory bodies of legal education in Malaysia must ensure that the remote communication technology is made a prerequisite in the teaching and learning of legal education. This is essential to prepare law students to embrace technology and to churn technology savvy law graduates for their future employability. As aptly noted by Tan Sri Datuk Seri Panglima Richard Malanjum, the former Chief Justice of Malaysia, at the Opening of the Legal Year 2019: ‘The legal profession must embrace technology. There is no option … . Adapt or be dropped … unless the Law schools start preparing their law graduates for the industry, they may end up in the unemployment queue’.